O serviço público federal brasileiro e a fábula do ataque das formigas gigantes - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The common sense remarks that Brazilian public service has a chronic oversize, a characteristic of a patronage and entrenched patrimonialism and partisanship. This paper shows evidences that refute this common sense. In addition, the paper offers recommendations and proposals to overcome this vulgarized perception. The responsibility to discuss the role, image and also the size of Brazilian State is a strategic challenge to move forward to the improvement of public services, with the guarantee of rights and inclusive development. Aligned with the idea of active transparency, it is proposed to offer regular and proper information about Brazilian public service, through systematic processes of accountability; the formulation of a ten-year plan of organization, qualification and innovation of public service; and the creation of an observatory of public service.
Keywords: H11; H60; 330; State; public administration; civil service; people management